Health and Medicine in the Islamic Tradition: Change and Identity By Fazlur Rahman; New York: The Crossroad Publishing Company, 1987, xiii + 149 pp. (American Journal of Islam and Society, 1990)
The late Dr. Fazlur Rahman, Harold H. Swift Distinguished Service Professor of Islamic Thought at the Oriental Institute of the University of Chicago, has written this book as number seven in the series on Health/Medicine and the Faith Traditions. This series has been sponsored as an interfaith program by The Park Ridge Center, an Institute for the study of health, faith, and ethics. Professor Rahman has stated that his study is "an attempt to portray the relationship of Islam as a system of faith and as a tradition to human health and health care: What value does Islam attach to human well-being-spiritual, mental, and physical-and what inspiration has it given Muslims to realize that value?" (xiii). Although he makes it quite clear that he has not attempted to write a history of medicine in Islam, readers will find considerable depth in his treatment of the historical development of medicine under the influence of Islamic traditions. The book begins with a general historical introduction to Islam, meant primarily for readers with limited background and understanding of Islam. Following the introduction are six chapters devoted to the concepts of wellness and illness in Islamic thought, the religious valuation of medicine in Islam, an overview of Prophetic Medicine, Islamic approaches to medical care and medical ethics, and the relationship of the concepts of birth, contraception, abortion, sexuality, and death to well-being in Islamic culture. The basis for Dr. Rahman's study rests on the explication of the concepts of well-being, illness, suffering, and destiny in the Islamic worldview. He describes Islam as a system of faith with strong traditions linking that faith with concepts of human health and systems for providing health care. He explains the value which Islam attaches to human spiritual, mental, and physical well-being. Aspects of spiritual medicine in the Islamic tradition are explained. The dietary Jaws and other orthodox restrictions are described as part of Prophetic Medicine. The religious valuation of medicine based on the Hadith is compared and contrasted with that found in the scientific medical tradition. The history of institutionalized medical care in the Islamic World is traced to awqaf, pious endowments used to support health services, hospices, mosques, and educational institutions. Dr. Rahman then describes the ...